Preventive role of lowmolecularweight heparin in unexplained recurrent pregnancy loss - M A Khan; E S Khan; A Basharat; M Jamil; S Ayub (South African Medical Association, 2017)
Background. Recurrent pregnancy loss (RPL) is a source of great distress for couples, and the search continues for an intervention to improve live birth rates in affected women. A daily injection of low-molecular-weight heparin (LMWH) is often prescribed to women with unexplained RPL, although evidence suggesting a benefit is limited.Objective. To compare the efficacy of LMWH with a placebo in terms of live birth rates in women with unexplained RPL.Methods. All pregnant females between 18 and 44 years of age who reported at the unit of obstetrics and gynaecology, Shifa International Hospital, Islamabad, during April 2013 to January 2014, who had a history of â‰¥2 consecutive first trimester pregnancy losses were enrolled. All participants were randomly allocated to one of two groups. Group A received a daily dose of 40 mg enoxaparin (LMWH) subcutaneously and group B women received a placebo in the form of multivitamin tablets. Efficacy was defined in terms of live births after the age of viability (i.e. 24 weeksâ€™ gestation) and was compared in both treatment and control groups. Risk estimation was also performed and relative risk (RR) along with 95% confidence interval (CI) was calculated.Results. The groups were similar in terms of mean age, gestational age and body mass index. Our results showed no statistically significant difference in live birth rates between the two groups, with 78.8% and 73.8% for group A and B, respectively (p=0.0574). A RR of 1.07 (95% CI 0.9 - 1.3) was calculated for group A.Conclusion. Subcutaneous enoxaparin in a once daily dose of 40 mg did not improve the chance of live births in nonthrombophilic women with unexplained RPL when compared with the placebo.